Cut-off points of the Ishii test to diagnosing severe sarcopenia among multi-ethnic middle-aged to older adults: results from the West China Health and Aging Trend study - Luo, Shuyue; Chen, Xiaoyan; Hou, Lisha; Yue, Jirong; Liu, Xiaolei; Xia, Xin; Cao, Li; Dong, Birong (Frontiers in Medicine, 2023)
Abstract OBJECTIVES: This study was designed to establish the diagnostic utility of the Ishii test, which gauges the odds of severe sarcopenia based on the results of an equation based upon age, grip strength, and calf circumference among middle-aged and older adults in Western China. METHODS: This study incorporated adults ≥ 50 years of age from the West China Health and Aging Trend (WCHAT) study. Severe sarcopenia was defined as per the Asian Working Group for Sarcopenia: 2019 Consensus(AWGS2019) recommendations, with the odds of severe sarcopenia being estimated with the Ishii test score chart. The diagnostic utility of the Ishii test in this patient cohort was assessed by analyzing its sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and the area under the ROC curve (AUC). RESULTS: In total, 4,177 individuals ≥ 50 years of age were included in this study including 2,688 females (63.9%) and 1,509 males (36.1%). These included 568 (13.6%) participants affected by severe sarcopenia, of whom 237 were male (15.7%) and 331 were female (12.4%). Optimal Ishii test cut-off values established based on Youden’s index were ≥ 114 for males and ≥ 120 for females when using the AWGS2019 reference standard. The sensitivity/specificity/PPV/NPV of the Ishii test when screening for severe sarcopenia were 89.45%/77.15%/0.42/0.98 in males and 90.03%/ 77.05%/0.36/0.98 in females. The AUC values for the Ishii test in males and females were 0.899 (95% CI, 0.883-0.916) and 0.905 (95% CI, 0.892-0.917), respectively. CONCLUSION: These data indicate that the Ishii test offers value as a candidate diagnostic test that can be used to screen for severe sarcopenia, with recommended diagnostic cut-off values of ≥ 114 for males and ≥ 120 for females.